2005
DOI: 10.1074/jbc.m506397200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with the Na,K-ATPase and Tissue Distribution of FXYD5 (Related to Ion Channel)

Abstract: FXYD5 (related to ion channel, dysadherin) is a member of the FXYD family of single span type I membrane proteins. Five members of this group have been shown to interact with the Na,KATPase and to modulate its properties. However, FXYD5 is structurally different from other family members and has been suggested to play a role in regulating E-cadherin and promoting metastasis (Ino, Y., Gotoh, M., Sakamoto, M., Tsukagoshi, K., and Hirohashi, S. (2002) Proc. Natl. Acad. Sci. U. S. A. 99, 365-370). The goal of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
132
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(144 citation statements)
references
References 36 publications
(36 reference statements)
10
132
0
2
Order By: Relevance
“…It is located at chromosome 19 and has a single transmembrane domain. It interacts with and modulates the properties of the Na þ , K þ ATPase (Ino et al, 2002;Lubarski et al, 2005). In human tissues increased dysadherin expression has been correlated with the development of metastasis and poor prognosis in gastric, pancreatic, colorectal, oesophageal, thyroid, tongue and cervical carcinomas, as well as in malignant melanoma (Aoki et al, 2003;Sato et al, 2003;Shimamura et al, 2003Shimamura et al, , 2004Nakanishi et al, 2004;Shimada et al, 2004a, b;Wu et al, 2004;Batistatou et al, 2005Batistatou et al, , 2006Nishizawa et al, 2005;Kyzas et al, 2006).…”
Section: Dysadherin In Breast Carcinomamentioning
confidence: 99%
“…It is located at chromosome 19 and has a single transmembrane domain. It interacts with and modulates the properties of the Na þ , K þ ATPase (Ino et al, 2002;Lubarski et al, 2005). In human tissues increased dysadherin expression has been correlated with the development of metastasis and poor prognosis in gastric, pancreatic, colorectal, oesophageal, thyroid, tongue and cervical carcinomas, as well as in malignant melanoma (Aoki et al, 2003;Sato et al, 2003;Shimamura et al, 2003Shimamura et al, , 2004Nakanishi et al, 2004;Shimada et al, 2004a, b;Wu et al, 2004;Batistatou et al, 2005Batistatou et al, , 2006Nishizawa et al, 2005;Kyzas et al, 2006).…”
Section: Dysadherin In Breast Carcinomamentioning
confidence: 99%
“…A related effect has also been observed in renal cell carcinoma cells (7). CCL2 (also termed MCP-1 2 for monocyte chemotactic protein-1) is a small cytokine belonging to the CC chemokine family. It participates in monocyte recruitment during infection or under other inflammatory conditions (13).…”
mentioning
confidence: 93%
“…In our previous publication (2), we have shown that FXYD5 can be found in normal cells and that it is particularly abundant in epithelial cells in kidney, intestine, and lung. These epithelia are directly exposed to different levels of bacterial pathogens, present as contaminants in food or in airborne particles.…”
Section: Fxyd5 Effect On Ccl2 Secretion Is Not Exclusive To M1mentioning
confidence: 99%
See 2 more Smart Citations